Female directors on corporate boards: does female leadership drive corporate environmental transparency? - Siew, Michelle Huei Phua; Ho, Poh-Ling (2017)
This paper examines the role of female directors on corporate boardroom on the extent of corporate environmental disclosure (CED) of 260 Malaysian listed companies in year 2013. Resource dependence theory is utilized as the theoretical framework to explain the role of female directors on corporate boards.Content analysis is employed to gauge the extent of CED based on a self-constructed index that is derived from Global Reporting Initiatives (GRI) and prior studies.Multiple regression is conducted and findings revealed that female directors’ presence and female holding multiple directorships to be significant predictors of extent of CED.The findings lend support to the resource dependence theory on the contribution of board gender diversity and are useful for both policy makers and regulators.